PREPARASI NANOSOL Ag/TiO2/SiO2 SEBAGAI LAPIS TIPIS FUNGSIONAL PADA KAIN KATUN UNTUK DEGRADASI ERITROSIN - , PRAYOGA WAHYU TRIPUTRA, Dr. Eko Sri Kunarti, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Preparation and characterisation of Ag/TiO2/SiO2 nanosol as a cotton functional thin layer as well as its activity test as a photocatalyst for the degradation of erythrosine stain have been carried out in this research. The preparation was conducted by sol-gel method at room temperature by using TiCl4, rice husk ash, and AgNO3 as the sources of TiO2, SiO2, and Ag+ solution with ratios of Ti/Si (1, 2, and 3) and Ag/Ti = 0.05. The characterisations were performed by infrared spectroscopy, X-ray diffraction, UV-visible specular reflectance spectrometry, transmission electron microscopy, and X-ray flourescence spectrometry methods. The activity tests were done in a batch system in a closed reactor equipped with UV and visible lamps. The percentage of degradation of erythrosine before and after its process was determined by using UV-visible spectrometers. Results showed that Ag/TiO2/SiO2 nanosol was well deposited on cotton to form Ag/TiO2/SiO2 thin layer with ratios of Ti/Si and Ag/Ti were 2 and 0.05. The Ag/TiO2/SiO2 thin layer could optimally degrade the erythrosine stain at pH of 7 and irradiation time of 8 hours with the degradation percentage of 81.06 % with Ag : Ti/Si = 0.05 : 2 under UV light and 62.80 % under UV with Ti/Si = 2.